Interest of Student In Futsal at SMP Negeri 32 Makassar - Hamid, Tri Wardani; Bismar, Ahmad Rum; Nawir, Nukhrawi (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This study aims to determine students’ interest in futsal sports in students of SMP Negeri 32 Makassar, Makassar City Regency. This study is descriptive with a single variable. Student interest in futsal sports in students of SMP Negeri 32 Makassar. A random sample of 40 students was selected. The data collection technique uses questionnaires to determine students’ interest in futsal sports in students of SMP Negeri 32 Makassar. Furthermore, the data obtained were analyzed using percentage descriptive analysis, with the help of computers through the SPSS program. The results showed that student interest in futsal sports in SMP Negeri 32 Makassar students was high with a percentage reaching 66.54% which was influenced by several indicators of interest such as motivation and ideals, attitudes towards teachers and lessons, family support, facilities and others. The conclusion that can be drawn from the results of this study is that students already have a good interest in futsal sports in students of SMP Negeri 32 Makassar, Makassar City Regency.